Azaphenothiazine Conjugates: A New Class of Antimicrobial Compounds - Kushwaha K.; Buchanan D.; Nkosi A.; Jangra J.; Kumar R.; Singh S.K.; Jain S.C.; Panda S.S. (My University, 2025)
Although phenothiazines have been widely explored in medicinal chemistry for over a century, little attention has been paid to their pyridine analogs, azaphenothiazines. This article reports the first synthesis, characterization, and antimicrobial evaluation of S-oxide analogs of N-aminoalkylated azaphenothiazines as antibacterials and antifungals. The optimized synthetic protocol enabled the production of the desired azaphenothiazine sulfoxides 12a–e and sulfonyls 14a–e, respectively. In addition to the x-ray crystal structure of azaphenothiazine sulfoxide intermediate 10, each target compound was characterized using spectroscopy techniques. All of these were investigated in vitro for antibacterial and antifungal activity against several strains of bacteria and fungi. Biological assays revealed selective antibacterial activity, with sulfoxides (12a–e) exhibiting broad inhibition and sulfones (14a–e) showing selectivity toward gram-negative bacteria. Compound 12c demonstrated fourfold higher potency against Escherichia coli than the reference drug. In antifungal studies, compound 14c showed the highest activity (MIC 1.2 µg/mL against Candida albicans). Our in silico evaluations utilized molecular dynamic (MD) and docking studies for active-site binding simulations, revealing favorable drug-like properties and pharmacokinetics. Finally, toxicology assays determined all synthesized analogs to be non-toxic to kidney and hepatic tissues. This report highlights the newly described S-oxide azaphenothiazine conjugates and their potential as potent antimicrobial agents. © 2025 Wiley-VHCA AG, Zurich, Switzerland.